Technology, Pedagogy and Content Knowledge Model for Increasing Civic Education Teacher’s Competencies in the Classroom - Luthfi, Zaky Farid; Wijayanto, Bayu; Novariza, Rika; Muttaqiin, Arief; Waldi, Atri (Journal of Moral and Civic Education, 2023)
The Covid-19 pandemic has required students to learn from home, leading teachers to adapt and develop online learning that integrates technological, pedagogical, and content knowledge (TPACK). This study aimed to investigate the knowledge and skills of social studies teachers at the middle and high school levels in transmitting TPACK. This study used a quantitative approach with a survey method, with a sample of 117 respondents from middle and high schools. The results showed no differences in skills between genders in using TPACK. Secondly, TPACK is the ability to integrate technology, pedagogy and content processing components, but the results show that teachers do not fully own these components.